2013
DOI: 10.1016/j.ijcard.2012.09.235
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular health status in Chinese adults in urban areas: Analysis of the Chinese Health Examination Database 2010

Abstract: About two-thirds of the adult Chinese urban population has "poor" cardiovascular health. Comprehensive individual and population-based interventions must be developed to improve cardiovascular health status in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
30
3
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 18 publications
10
30
3
1
Order By: Relevance
“…The prevalence of meeting all seven LSS has also been shown to be low in a variety of predominantly non-Hispanic white populations ranging from 0% to 1% only 2326 . Studies in Chinese populations also show low prevalence of meeting all 7 LSS (0.1% to 1.5%) 2729 .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of meeting all seven LSS has also been shown to be low in a variety of predominantly non-Hispanic white populations ranging from 0% to 1% only 2326 . Studies in Chinese populations also show low prevalence of meeting all 7 LSS (0.1% to 1.5%) 2729 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some previous studies have shown that there is a significant association between the low prevalence of ideal cardiovascular health metrics and incidence of CVD among adults, and meeting a greater number of ideal cardiovascular health metrics is associated with a significantly low risk for CVD [13, 19]. With the low prevalence of healthy factors and lifestyles, it can be expected that CVD will continue to increase in the near future if there is no intervention [20, 21], so it’s urgently required to develop comprehensive population-based interventions to achieve greater number of ideal cardiovascular health metrics.…”
Section: Discussionmentioning
confidence: 99%
“…Considerando a análise agregada dos indicadores, resultados de estudos internacionais que aplicaram o escore proposto pela American Heart Association também mostraram prevalên-cias muito baixas, com diferenças entres os sexos 22,23,24,34,35,36 . Diferentemente dos resultados encontrados em populações americanas 23,35 , em nosso estudo o cenário foi desfavorável às mulheres, marcado pelo pior desempenho no índice de fatores comportamentais, porém os homens apresentaram pior desempenho no ín-dice de fatores biológicos.…”
Section: Discussionunclassified